MECHANICAL DAMAGE TO COTTON FIBER DURING PRIMARY PROCESSING OF RAW COTTON (Web of Technology: Multidimensional Research Journal, 2025)
The article presents analyses of mechanical damage to cotton fiber and its impact on quality during technological transitions at a cotton ginning plant.